2011
DOI: 10.1007/s11134-011-9264-8
|View full text |Cite
|
Sign up to set email alerts
|

Monotonicity properties of user equilibrium policies for parallel batch systems

Abstract: We study a simple network with two parallel batch-service queues, where service at a queue commences when the batch is full and each queue is served by infinitely many servers. A stream of general arrivals observe the current state of the system on arrival and choose which queue to join to minimize their own expected transit time. We show that for each set of parameter values there exists a unique user equilibrium policy and that it possesses various monotonicity properties. User equilibrium policies for proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Wang et al [22] studied the strategic behavior of passengers in the queueing system with batch transfer under threshold policy and obtained the threshold joining strategies of passengers. Afimeimounga et al [23], Chen et al [24], and the references therein are recommended for the interested readers who want to know more about the customer behavior analysis in batch queueing systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wang et al [22] studied the strategic behavior of passengers in the queueing system with batch transfer under threshold policy and obtained the threshold joining strategies of passengers. Afimeimounga et al [23], Chen et al [24], and the references therein are recommended for the interested readers who want to know more about the customer behavior analysis in batch queueing systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most papers in this area are motivated by transportation systems (see, for example, the introductory example in Section 1.5 of Hassin and Haviv [32]). More concretely, a first thread of research deals with strategic customer routing behavior in networks with infinite server systems with batches and single-server systems with single services (see, for example, Calvert [14], Afimeimounga et al [3,4], Afimeimounga [2], Chen et al [16], and Wang and Ziedins [44]). These works have shown the occurrence of Downs-Thompson and Braess-type paradoxes in the context of simple queueing networks (for a thorough overview, see Hassin [30], Chapters 8.6 and 8.7).…”
Section: Literature Reviewmentioning
confidence: 99%
“…• Choice among multiple capacity services. Several studies have been conducted on the strategic choice among infinite server systems with regular batches and single-server systems of single service [37][38][39][40][41]. These studies showed interesting Downs-Thompson and Braess-type paradoxes through the equilibrium analyses of this type of model.…”
mentioning
confidence: 99%